2011
DOI: 10.1080/10942910903456978
|View full text |Cite
|
Sign up to set email alerts
|

Shift of pH-Value During Thermal Treatments in Buffer Solutions and Selected Foods

Abstract: The pH value is one of the most important process parameters during thermal treatments, regardless if the medium is a simple buffer solution or a complex food matrix. When the temperature increases after an initial measurement of the pH at ambient temperature (25 • C), a significant pH shift could occur, which could produce incomparable results in different buffer solutions or lead to side reactions during food preservation. Consequently, a measurement cell was constructed to record online the pH-value and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 21 publications
5
33
0
Order By: Relevance
“…The slopes of the pH decrease over temperature were not significantly different (P≥0.05) for all the media examined except for whole milk against MCC with 3.3% protein. Walstra (2006) The decrease of the pH of milk, milk concentrates, and casein solutions with increasing temperature was already described in literature (Anema 2009;Chaplin and Lyster 1988;Reineke et al 2011) and the slopes were in the same range as the slopes observed in this study. The decrease of pH in milk and milk concentrate was attributed to the changing dissociation of ions and the supersaturation of calcium phosphate (Anema 2009;Walstra et al 2006).…”
Section: Buffering Capacity and Ph Development During Heatingsupporting
confidence: 80%
See 4 more Smart Citations
“…The slopes of the pH decrease over temperature were not significantly different (P≥0.05) for all the media examined except for whole milk against MCC with 3.3% protein. Walstra (2006) The decrease of the pH of milk, milk concentrates, and casein solutions with increasing temperature was already described in literature (Anema 2009;Chaplin and Lyster 1988;Reineke et al 2011) and the slopes were in the same range as the slopes observed in this study. The decrease of pH in milk and milk concentrate was attributed to the changing dissociation of ions and the supersaturation of calcium phosphate (Anema 2009;Walstra et al 2006).…”
Section: Buffering Capacity and Ph Development During Heatingsupporting
confidence: 80%
“…It changes with increasing temperature. The pH value during heating can increase, decrease, or stay constant, depending on the buffer system (Reineke et al 2011). The pH development influences the heat resistance of spores.…”
Section: Buffering Capacity and Ph Development During Heatingmentioning
confidence: 99%
See 3 more Smart Citations